2020
DOI: 10.1109/jsen.2019.2946854
|View full text |Cite
|
Sign up to set email alerts
|

Low-Impedance PEDOT:PSS MEA Integrated in a Stretchable Organ-on-Chip Device

Abstract: We present the first Organ-on-Chip equipped with a low-impedance Poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) MicroElectrode Array (MEA). The novel device allows simultaneous mechanical stimulation with a stretchable PDMS membrane and electrical monitoring via the PEDOT:PSS MEA of multiple in vitro cell cultures. The surface area enhancement and the morphology of the PEDOT:PSS allows an increase of the charge injection per unit area at the electrode-electrolyte interface, resulting in sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…An alternative material that has been widely used to monitor cellular activity in a wide range of device architectures in vitro systems is the organic semiconductor polymer poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonate (PEDOT:PSS). 32,33 For impedance measurements, PEDOT:PSS has been used to improve the recording performance of opaque electrodes 34,35 since it is less affected by electrode polarization impedance compared to inorganic materials. Furthermore, PEDOT:PSS has also been employed to record electrical activity and perform optical imaging simultaneously in microelectrodes array due to its excellent compromise between the polymer electrical properties and transparency.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative material that has been widely used to monitor cellular activity in a wide range of device architectures in vitro systems is the organic semiconductor polymer poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonate (PEDOT:PSS). 32,33 For impedance measurements, PEDOT:PSS has been used to improve the recording performance of opaque electrodes 34,35 since it is less affected by electrode polarization impedance compared to inorganic materials. Furthermore, PEDOT:PSS has also been employed to record electrical activity and perform optical imaging simultaneously in microelectrodes array due to its excellent compromise between the polymer electrical properties and transparency.…”
Section: Introductionmentioning
confidence: 99%
“…have reported an impedance reduction of 15 times for Ø30 µm PEDOT:PSS covered Pt electrodes. [ 50 ] Ganji et al. have observed a reduction of the impedance of 25 times for medium‐sized electrodes (Ø20 µm); however, they reported a reduction of only 20 times for bigger electrodes (Ø80 µm).…”
Section: Resultsmentioning
confidence: 99%
“…Waafi et al have reported an impedance reduction of 15 times for Ø30 μm PEDOT:PSS covered Pt electrodes. [50] Ganji et al have observed a reduction of the impedance of 25 times for medium-sized electrodes (Ø20 μm); however, they reported a reduction of only 20 times for bigger electrodes (Ø80 μm). [46] The impedance reduction we report for all diameters, along with the calculated specific impedance (see Table 1), indicate that our PEDOT:PSS coated electrodes can be considered at the state-ofthe-art when compared to the literature.…”
Section: Recording and Stimulation Performances Of Planar Microelectr...mentioning
confidence: 98%
“…Another advantage of PEDOT is its versatility in being doped by various synthetic dopants, like PSS, further increasing the stability of recordings/stimulations in in vitro cultures, or even the internalization of biological dopants into its constitution, improving the fusing of the cell plasma membrane with the microelectrodes surface, thus improving the seal resistance. [ 99–106 ] In another angle, the attenuation of the signals acquired by MEAs due to their increased impedance, could be improved by changing the type of recording devices from passive to the use of nano‐FETs, such as the ones developed by Zhao et al. [ 83 ]…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of PEDOT is its versatility in being doped by various synthetic dopants, like PSS, further increasing the stability of recordings/stimulations in in vitro cultures, or even the internalization of biological dopants into its constitution, improving the fusing of the cell plasma membrane with the microelectrodes surface, thus improving the seal resistance. [99][100][101][102][103][104][105][106] In another angle, the attenuation of the signals acquired by MEAs due to their increased impedance, could be improved by changing the type of recording devices from passive to the use of nano-FETs, such as the ones developed by Zhao et al [83] Although the use of novel vertical 3D nanoelectrodes has presented researchers the capability of attenuated intracellular recordings for cardiomyocites, myotubes, and even human embryonic cells, the attempts to use the same devices in mammalian neurons have been unsatisfying and also scarce, as observed in the chart of Figure 23. This can be explained by the lowered probability of cell positioning with the small mammalian neurons in vertical structures in contrast to large planar electrodes (although confined to extracellular stimulation/ recording) and to the considerably bigger cardiomyocite cells which have a higher probability of providing successful coupling with 3D vertical electrodes.…”
Section: Discussionmentioning
confidence: 99%